ANALYSIS OF SPEAKING MATERIAL IN ENGLISH TEXTBOOK AT GRADE XII PUBLISHED BY KEMENDIKBUD 2018 - Utami, Lusi Tri; Syahid, Abdul; Sugianto, Aris (PROJECT (Professional Journal of English Education), 2021)
In a learning process of learning English, teaching materials are needed to support the learning process such as textbooks. Therefore, this research analysed English speaking material in “Bahasa Inggris” English textbook for twelfth grade of Senior High School Published by Kemendikbud 2018. The research problem of the study were: (1) What types of speaking material are there in “Bahasa Inggris” English textbook?, and (2) How is the content of the material on speaking English textbook for twelfth grades published by Indonesian government?. Therefore, the purposes of this study were: (1) To describe types of speaking material in “Bahasa Inggris” English Textbook., and (2) To identify the contain of material of speaking skills found in English textbook for twelfth graders published by Indonesian government. In carrying out this research, researcher used a qualitative approach with content analysis method. Data collected by carrying out evaluation checklist, interview, and documentation. The main research findings were: (1) The speaking materials contained in “Bahasa Inggris” English textbooks for twelfth graders published by Indonesian governmentcontains material in the form of dialogue, and (2) The speaking material in the book can help students based on the teacher's perspective and evaluation checklists. Keywords:  Speaking Material, Textbook Analysis, English Textbook